Selecting Treatment Modality for Small Hepatocellular Carcinoma: Radiofrequency Ablation, Percutaneous Alcohol and Acetic Acid Injection - Birry Karim; Andri Sanityoso Sulaiman (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2011)
Hepatocellular carcinoma (HCC) is the most common primary hepatic malignancy worldwide and is the leading cause of death in patients with cirrhosis. In early-stage tumors, potential curative therapies have been used including ablative therapies using percutaneous ethanol injection (PEI), percutaneous acetic acid injection (PAI) or radiofrequency ablation (RFA); surgical resection and liver transplantation. RFA is more effective and safer than other local ablative therapy modalities. RFA should be considered as the first-line treatment for patients with small HCC, i.e. sized less than 5 cm; preferably less than or equal to 3 cm since they are not suitable for liver resection or liver transplantation. RFA should also be compared with transarterial embolization, which currently has been considered as the standard HCC therapy in some countries. It has been reported that the combination of RFA and embolization treatment may reduce the early and late recurrence rate. Keywords: hepatocellular carcinoma, percutaneous ethanol injection, acetic acid injection, radiofrequency ablation